Council tax support schemes in England: What did local authorities choose, and with what effects? - Stuart Adam; James Browne; William Jeffs; Robert Joyce (Institute for Fiscal Studies (IFS), 2014)
Council tax benefit (CTB) was abolished in April 2013 and local authorities in England were charged with designing their own council tax support (CTS) schemes in its place. Although these must maintain support for pensioners at its previous level, local authorities have had wide discretion to design their own schemes for working-age families. This report analyses the CTS schemes that local authorities adopted in the first year of the new policy.
Keywords: 330